2020
DOI: 10.1021/acs.macromol.9b02280
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Structural Characterization of Biobased Diallyl–Eugenol Polymer Networks

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 61 publications
2
27
0
1
Order By: Relevance
“…These values are fairly similar between each other, confirming again that both series are analogous to each other structurally. Similar results on non‐zero y‐intercepts have been found for crosslinked polymers and have been attributed to physical entanglements. Indeed, 1 H DQ NMR experiments are able to probe and quantify such entanglements as their relaxation times are comparable to the NMR measuring window time (i. e. range of microseconds) which is not the case for DMA, as physical entanglements relax faster than the technique measuring window time (i. e. 1 Hz=1 s) …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…These values are fairly similar between each other, confirming again that both series are analogous to each other structurally. Similar results on non‐zero y‐intercepts have been found for crosslinked polymers and have been attributed to physical entanglements. Indeed, 1 H DQ NMR experiments are able to probe and quantify such entanglements as their relaxation times are comparable to the NMR measuring window time (i. e. range of microseconds) which is not the case for DMA, as physical entanglements relax faster than the technique measuring window time (i. e. 1 Hz=1 s) …”
Section: Resultssupporting
confidence: 84%
“…Nevertheless, these investigations did not address in detail the influence of the materials structure on their macroscopic functional properties. In that regard, 1 H DQ has been successfully used in combination with DMA measurements, to study Poly(trimethylene carbonate) (PTMC) and Eugenol‐based networks . Both polymers are highly‐crosslinked materials with both investigations successfully demonstrated a good agreement between the materials network structure and their macroscopic properties.…”
Section: Introductionmentioning
confidence: 99%
“…According to Flory’s theory, , the cross-link density ( ν ) of the material is directly related to the storage modulus in the rubber region and can be calculated based on the equation where E ′ is the storage modulus in the rubbery region, R is the gas constant, and T is the absolute temperature. For a more accurate determination of the cross-link density ( ν ), the values of the storage modulus ( E ′) were recorded at temperatures well above the glass transition temperature ( T g + 80 °C) of the analyzed materials. , The average molar mass between cross-links ( M C ) were calculated using the Tobolsky equation (eq )­ where ρ is the determined density (g·cm –3 ) and E ′ is the storage modulus in the rubbery plateau (MPa) at 130 °C. The obtained values for ν and M C are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…For a more accurate determination of the cross-link density (ν), the values of the storage modulus (E′) were recorded at temperatures well above the glass transition temperature (T g + 80 °C) of the analyzed materials. 49,50 The average molar mass between crosslinks (M C ) were calculated using the Tobolsky 51 equation (eq 6)…”
mentioning
confidence: 99%
“…Neda et al reported the synthesis of allyl-etherified eugenol (AEG) using allyl bromide and sodium hydroxide (NaOH) in DMSO in high yield (96%) as depicted in Scheme . This synthetic strategy has been followed by several authors to obtain AEG. Other solvents such as acetone or DMF can be used in this synthesis producing similar yields. , The reaction can be performed with potassium carbonate (K 2 CO 3 ) as the base instead of NaOH, , leading also to high reaction yields. , However, anhydrous DMF was used as solvent, which is considered a harmful solvent, whereas the use of other solvents such as acetone caused a significatively drop in the reaction yield (56%) …”
Section: Eugenol: Reactivity and Functionalizationmentioning
confidence: 99%